Silicon Valley Bank Bankruptcy—Liquidity Risk Analysis Based on Financial Statements - Dong Jiayi (SHS Web of Conferences)
Silicon Valley Bank declared bankruptcy in March 2023, becoming the second largest bank failure in U.S. history. The event impacted global financial markets, causing many industries and countries asset losses and increased citizens concern. This paper examines the liquidity risk factors of SVB based on the bank’s bankruptcy. In particular, the financial statements of SVB for the years 2021 and 2022 are taken into account, along with the trends in the financial markets. It was found that SVB was over-invested in securities and had a potentially high-risk liability structure. Therefore, when the contractionary monetary policy be implemented by Federal Reserve to against inflation led to higher interest rates and clients’ concerns about SVB’s credibility, SVB’s clients requested withdrawals in a short period and securities losses leading to a severe liquidity problem, culminating in bank run and a declaration of bankruptcy. The impact of this event was huge. Naturally, the financial markets suffered the most, as evidenced by the losses of numerous other institutions and the drop in stock prices. Thus the banks have more realization about the liquidity risk management importance. Finally, this study suggests optimizing the asset-liability structure and strengthening the regulation of liquidity risk, assessing potential risks, and formulating more diversified strategies to cope with unknown crises.